2020
DOI: 10.3390/ani10091537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Oxide and Arginine on the Intestinal Microbiota and Immune Status of Weaned Pigs Subjected to High Ambient Temperature

Abstract: This study aimed to investigate the effect of the l-arginine (Arg) inclusion and different doses of ZnO on the growth performance, intestinal microbiota and integrity, and immune status of weaned pigs. A total of 180 pigs (28-day-old) were randomly allotted to six treatments with six replicate pens in each treatment and five pigs per pen. The dietary treatments were Con (1.1% Arg); P-Zn (1.1% Arg + 2500 mg Zn as ZnO/kg diet); ARG (1.6% Arg); ZnArg1 (500 mg of Zn as ZnO/kg diet + 1.6% Arg); ZnArg2 (1000 mg of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many studies have reported changes in intestinal bacteria of pigs caused by ZnO [ 29 , 30 ]. The mechanisms by which ZnO improves growth performance are not completely understood, but it might increase the intestinal absorpiteve capacity by increasing the villus height [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported changes in intestinal bacteria of pigs caused by ZnO [ 29 , 30 ]. The mechanisms by which ZnO improves growth performance are not completely understood, but it might increase the intestinal absorpiteve capacity by increasing the villus height [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is the HS-induced hepatic cellular apoptosis, which can affect the regulation of blood Cl − by the liver [53]. Supplementation of dietary antioxidants (vitamins and micro-minerals) has shown significant improvement on some of the blood biochemical parameters of pigs under various stressors [15,29,38,54]. In our study, the concentration of Cl − was significantly improved (p < 0.01) in HT2 pigs after 7 days of exposure, and slight improvements were also observed after 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolyzed yeast is an end-product of yeast extraction through hydrolysis, and it typically contains both yeast extract and yeast cell walls [7]. Feeding pigs a diet supplemented with hydrolysed yeast has been reported to improve growth performance, immunity, and antioxidant status, as well as ameliorate intestinal disorder and in ammation response during diarrhea condition [30][31][32].…”
Section: Introductionmentioning
confidence: 99%